Serial strain imaging in takotsubo syndrome with concomitant coronary artery disease. Issue 3 (4th May 2019) - Heyse, Alex; Anne, Florence; Lagae, Beatrice; Van Haver, Hilde; Van Durme, Frederik
ABSTRACT: We report a case of takotsubo syndrome (TTS) triggered by herpes encefalitis in the presence of significant triple vessel coronary artery disease (CAD). The typical ECG abnormalities, moderately elevated cardiac enzymes with disproportionally elevated brain natriuretic peptide (BNP) as well as the typical wall motion abnormalities on echocardiography and left ventricular (LV) angiography, were consistent with the diagnosis of TTS with concomitant CAD rather than an acute coronary syndrome. The normalization of the wall motion abnormalities, ejection fraction and longitudinal strain on serial echocardiography all support the diagnosis of takotsubo syndrome, especially in challenging cases.